Cangrelor versus crushed ticagrelor in patients with acute myocardial infarction and cardiogenic shock: rationale and design of the randomised, double-blind DAPT-SHOCK-AMI trial - Motovska, Zuzana; Hlinomaz, Ota; Mrozek, Jan; Kala, Petr; Geisler, Tobias; Hromadka, Milan; Akin, Ibrahim; Precek, Jan; Kettner, Jiri; Cervinka, Pavel; Montalescot, Gilles; Jarkovsky, Jiri; et al. (EuroIntervention, 2024)
Cardiogenic shock (CS) is a devastating and fatal complication of acute myocardial infarction (AMI). CS can affect the pharmacokinetics and pharmacodynamics of medications. The unique properties of cangrelor make it the optimal P2Y12 inhibitor for CS-AMI, in terms of both efficacy and safety. The DAPT-SHOCK-AMI trial (ClinicalTrials.gov: NCT03551964; EudraCT: 2018-002161-19) will assess the benefits of cangrelor in patients with an initial CS-AMI undergoing primary angioplasty. This randomised, multicentre, placebo-controlled trial of approximately 550 patients (with an allowed 10% increase) in 5 countries using a double-blind design will compare initial P2Y12 inhibitor treatment strategies in patients with CS-AMI of (A) intravenous cangrelor and (B) ticagrelor administered as crushed tablets at a loading dose of 180 mg. The primary clinical endpoint is a composite of all-cause death, myocardial infarction (MI), or stroke within 30 days. The main secondary endpoints are (1) the net clinical endpoint, defined as death, MI, urgent revascularisation of the infarct-related artery, stroke, or major bleeding as defined by the Bleeding Academic Research Consortium criteria; (2) cardiovascular-related death, MI, urgent revascularisation, or heart failure; (3) heart failure; and (4) cardiovascular-related death, all (1-4) within 1 year after study enrolment. A platelet reactivity study that tests the laboratory antiplatelet benefits of cangrelor, when given in addition to standard antiplatelet therapy, will be conducted using vasodilator-stimulated phosphoprotein phosphorylation. The primary laboratory endpoints are the periprocedural rate of onset and the proportion of patients who achieve effective P2Y12 inhibition. The DAPT-SHOCK-AMI study is the first randomised trial to evaluate the benefits of cangrelor in patients with CS-AMI.
Keywords: Randomized Controlled Trials as Topic; Female; ticagrelor; fosfoproteiny; výsledek terapie; ženské pohlaví; antagonisté purinergních receptorů P2Y; Multicenter Studies as Topic; lidé; dvojitá slepá metoda; Phosphoproteins; adenosinmonofosfát; koronární angioplastika; Platelet Aggregation Inhibitors; Treatment Outcome; Percutaneous Coronary Intervention; multicentrické studie jako téma; Double-Blind Method; Male; Purinergic P2Y Receptor Antagonists; Ticagrelor; Aged; Shock, Cardiogenic; Adenosine Monophosphate; randomizované kontrolované studie jako téma; Myocardial Infarction; inhibitory agregace trombocytů; Vasodilator-Stimulated Phosphoprotein; lidé středního věku; kardiogenní šok; fosfoprotein stimulovaný vazodilatátorem; senioři; mužské pohlaví; Middle Aged; infarkt myokardu; Humans